What makes coaches adopt canada`s long term athlete development model? Understanding the attributes of adoption by cross-country ski coaches - Frankish, M.; Beaudoin, C. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: This research project is part of the first Canadian study to examine the determinants of adoption of the Long Term Athlete Development (LTAD) model as experienced by sport coaches. We interviewed cross-country ski coaches to better understand the adoption of the LTAD model into their coaching practice. The LTAD is a sport developmental model "based on the physical, mental, emotional, and cognitive development of children and adolescents" (Canadian Sport Centers, 2006, p. 7). The model shows the interdependency of physical education, interscholastic sport, competitive sport, and recreational activity in order to encourage life-long participation on a national scale. We used Rogers' (2003) Diffusion of Innovations theory to understand how attributes of the LTAD model influenced Canadian cross-country ski coaches' decisions to adopt or reject the model into their coaching practice. The following questions guided the focus of the project: (1) what attributes of adoption do coaches perceive the LTAD model possessing, and (2) how do these attributes affect a coach's decision to adopt or reject the LTAD model? By addressing these questions, this project will create the first step in understanding how sport coaches' perceive the LTAD model and what influences them to adopt it into their coaching practice.